Women, poverty and adverse maternal outcomes in Nairobi, Kenya - Izugbara Chimaraoke O; Ngilangwa David P (BMC, 2010)
Abstract Background The link between poverty and adverse maternal outcomes has been studied largely by means of quantitative data. We explore poor urban Kenyan women's views and lived experiences of the relationship between economic disadvantage and unpleasant maternal outcomes. Method Secondary analysis of focus group discussions and in-depth individual interviews data with women in two slums in Nairobi, Kenya. Results Urban poor women in Nairobi associate poverty with adverse maternal outcomes. However, their accounts and lived experiences of the impact of poverty on maternal outcomes underscore dynamics other than those typically stressed in the extant literature. To them, poverty primarily generates adverse maternal outcomes by exposing women to exceedingly hard and heavy workloads during pregnancy and the period surrounding it; to intimate partner violence; as well as to inhospitable and unpleasant treatment by service providers. Conclusions Poverty has wider and more intricate implications for maternal outcomes than are acknowledged in extant research. To deliver their expected impact, current efforts to promote better maternal outcomes must be guided by a more thorough perspective of the link between women's livelihoods and their health and wellbeing.